DAMPAK KEBIJAKAN PELAYANAN KESEHATAN GRATIS TERHADAP KEPUASAN PASIEN DALAM MENERIMA PELAYANAN KESEHATAN PUSKESMAS DI KOTA AMBON - Lutfan Lazuardi, Lintje Sintje Corputty Hari Kusnanto (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The Mayor of Ambon City, in order to improvethe welfare of society especially the health sector has made apolicy too free basic health services costs at health centersand its network for all communities. In implementing this policy,there are many problems both tecnical and operational.Objectives: The objective of this research was to determinethe performance of officers in providing free health servicesto the public in accordance with the level of satisfaction interms of free health care.Methods: This research is descriptive analysis with aqualitative approach and conducted at five sub districtcoordinator public health services.Research data obtained byin-depth interviews and focused group discussion.For dataanalysis,qualitative techniques were used, that is, narrativeinterpretations, conclusions and data validation by triangulationtechniques.Results: The results show that on giving free services,officerdoes not show any improvement in their performance. Thiswas the result of the absence of incentives or specialcompensation for them. Material and non material compensationis expected to increase work motivation. Supporting facilitiessuch as logistics and health facilities should be prepared toimprove provision of free services, thus in turn increasingpatientâs satisfaction.Keywords: Free Health Services Policy, Performance,Incentive and Compensation, Patient Satisfaction.